A Short Review on Cefueoxime Axetil Tablet - Kumar, Sanjay; Jeet, Kamal; Devi, Anjana; Kumar, Pankaj; Kumar, Nishant (Asian Journal of Pharmaceutical Research and Development, 2022)
Cefuroxime axetil is a broad-spectrum antibiotic with a simple pharmacokinetic profile. The medicine treats otitis media, pharyngitis, sinusitis, CAP, and acute exacerbations of chronic bronchitis effectively and well. Cefuroxime axetil was beneficial in intravenous/oral sequential therapy for CAP, but dosage recommendations are not accessible in some countries. Cefuroxime axetil may be used to treat community-acquired infections, including those caused by -lactamase-producing respiratory bacteria. In an era of rapidly growing bacterial resistance, empirical treatment with cefuroxime axetil may assure the proper use of newer antibacterial medicines, reducing bacterial resistance to these drugs.